Plasmonic nanopillar coupled two-dimensional random medium for broadband light trapping and harvesting - Bingi, Jayachandra (2015)
Random textures have proven to be a better option for light localization and energy harvesting in solar cells. On the other hand, plasmonic structures are significant in localizing the fields into submicron domains. We propose a layered structure design that contains the random dielectric medium with a plasmonic nanopillars array as a back reflector, followed by demonstrating its efficient light trapping ability through simulation means. This structure has shown significant enhancement in the broadband absorption of the light spectrum in the wavelength range UV-IR and a higher extinction in the near-infrared wavelengths. The structure also shows the dependence of reflection on the nanopillar height as well as localization in the nanopillar region. The broadened and red shifted plasmonic nanopillar resonances (transverse and longitudinal) in a high-index medium are shown as the reasons for enhanced broadband absorption.